Development of Education in Early Childhood in the Digital Era - Regina Aprilia Rusliana (Universitas Negeri Padang, 2019)
Industrial Revolution Era 4.0 is an era faced by Indonesia today. The era where life is always associated with technology and information. Based on an initial evaluation of the country's readiness to face the industrial revolution 4.0 Indonesia is estimated as a country with high potential. From this, it can be said that Indonesia must be ready to face the industrial revolution 4.0. Current technological developments continue to advance rapidly, the world enters the 4.0 era marked by the emergence of the 4th industrial revolution, starting with the internet revolution in the 90s. In the 4.0 era, one of the smart technologies that is very popular with the public is the gadget. This can simply be interpreted as a device or electronic device that has multiple functions. Various forms of gadgets such as smartphones, tablets, laptops, and so on. In the digital era now, educating children is quite difficult. Because technological development is accelerating and making it easier for humans, the development of millennial technology demands to continue to monitor children in their activities related to technology, the world of education must educate children as early as possible to anticipate various negative influences in the digital era.Keywords: Early Childhood Education, Digital Era